The role of RIPK3 in the crosstalk between hepatocytes and macrophages in metabolic-dysfunction associated steatotic liver disease - Alves, Mariana Isabel Francisco (2023)
Tese de mestrado, Ciências Biofarmacêuticas, 2023, Universidade de Lisboa, Faculdade de Farmácia.